The transmembrane domain is a primary determinant of the location and substrate specificity in cyanobacterial FtsH heterocomplexes - Yi,L; Kulik,N; Shao,S; Nixon,PJ; Komenda,J; Krynická,V; Yu,J; Liu,B (Algal Research, 2026)
Membrane-embedded FtsH proteases play important and diverse physiological roles in prokaryotes, chloroplasts and mitochondria, but how substrates are distinguished remains unclear. The cyanobacterium Synechocystis sp. PCC 6803 contains four FtsH homologs organized into two distinct heterocomplexes and one homocomplex. The two heterocomplexes, derived from a recent gene duplication event, are the essential FtsH1/3 complex found in the cytoplasmic membrane, and the thylakoid-embedded FtsH2/3 complex, with a role in the repair of photodamaged photosystem II. Using a domain swapping approach, we demonstrate here that the transmembrane domains of FtsH1 and FtsH2 are primary determinants of the cellular location and functional differences between the FtsH1/3 and FtsH2/3 complexes, whereas the soluble AAA+ (ATPases associated with diverse cellular activities) and protease domains and the soluble linker were largely interchangeable under the conditions tested. Overall, our findings identify the transmembrane domain as an important determinant of both the location and substrate specificity of FtsH heterocomplexes and support a role for this domain in their functional evolution.